Die Skrif is aan ons toevertrou: Die implikasie van τὰ λόγια τοῦ θεοῦ in Romeine 3:2 - Zuiddam, Benno Alexander (HTS teologiese studies, 2010)
In Paul’s Epistle to the Romans, the expression τὰ λόγια τοῦ θεοῦ refers to speech of God that was entrusted to the Jews as a people. This includes everything He spoke through Moses and the prophets. The apostle presents this as a matter of the greatest privilege to his readers, both for its authoritative contents and the personal involvement of the God of the Covenant it represents. Paul uses these ‘oracles’ or ‘very words of God’ as a collective reference (indicated by τὰ) to all divine speech that was entrusted to the Jews before the revelation of God’s righteousness in Christ, to which these λόγια τοῦ θεοῦ bore witness in advance. This article consequently argues that τὰ λόγια τοῦ θεοῦ refers to the Bible as phenomenon, the revealed Word of God that was entrusted to the Jewish people.